ESG APPROACHES TO ENSURING BANK FINANCIAL STABILITY IN THE SUSTAINABLE FINANCE SYSTEM - Pakhnenko, Olena; Uzlova, Anastasiia; Minenko, Hlib (Current Problems of Sustainable Development, 2026)
The article examines ESG approaches to ensuring bank financial stability under the transformation of the sustainable finance system. The purpose of the study is to substantiate the channels through which environmental, social and governance factors influence bank financial stability. The article identifies six interrelated channels of ESG impact: the risk channel, the information channel, the financial resources channel, the operational efficiency channel, the adaptability channel and the institutional-regulatory channel. ESG factors influence bank financial stability indirectly, through changes in the bank’s risk profile, the quality of managerial decisions, the stability of the funding base, the cost of capital, stakeholder trust and the ability to withstand external shocks. The risk channel is related to the integration of ESG criteria into credit analysis and the improvement of loan portfolio quality. The information channel reflects the role of ESG disclosure in reducing information asymmetry and strengthening stakeholder confidence. The financial resources channel explains how a stronger ESG profile can improve access to funding and increase financial flexibility. ESG factors may also support bank financial stability through higher operational efficiency, better internal control, human capital development, technological resilience and cybersecurity. The adaptability channel highlights the role of ESG approaches in strengthening long-term resilience to climate, macroeconomic, regulatory, geopolitical and technological shocks. The institutional-regulatory channel reflects the transition of ESG from voluntary practices to supervisory expectations and regulatory requirements. The identified channels are consistent with the approaches of the National Bank of Ukraine to ESG risk management. It is emphasized that the positive impact of ESG approaches on bank financial stability is not automatic. Formal or fragmented ESG implementation may generate additional costs and increase operational or reputational risks. Therefore, ESG factors can strengthen bank financial stability only if they are systematically integrated into credit analysis, risk management, corporate governance, strategic planning, internal control and ESG risk disclosure.
Keywords: bank financial stability; ESG factors; sustainable finance; banking sector; risk management; banking regulation